Venus and Her Companions (Hor. Carm. 1. 30) - Egorova, Sofia (Hyperboreus, 2022)
In Carm. 1. 30, Horace lists the companions of Venus, naming among them the usual characters for this context – Cupid, Graces, nymphs, as well as the personification of Youth and – which is very unusual – Mercury. Since antiquity, commentators have offered various explanations of his appearance here, and several recent works have suggested correlating the scene of the appearance of the goddess and her suite with works of ancient art. In this vein, the author proposes that Horace was inspired not by an elongated composition with a procession of deities, but by the way the figures were arranged in wall paintings (for example, Villa Farnesina, Cubiculum B), in which two smaller side panels (in our case with one figure of Youth/Hebe and Mercury) were placed to the sides of the central multifigure group (Venus, Cupid, Graces, nymphs).